Twelve years a slave - Northup, Solomon, 1808-1863? (Penguin Books, 2013)
Perhaps the best written of all the slave narratives, Twelve Years a Slave is a harrowing memoir about one of the darkest periods in American history. It recounts how Solomon Northup, born a free man in New York, was lured to Washington, D.C., in 1841 with the promise of fast money, then drugged and beaten and sold into slavery. He spent the next twelve years of his life in captivity on a Louisiana cotton plantation. After his rescue, Northup published this exceptionally vivid and detailed account of slave life. It became an immediate bestseller and today is recognized for its unusual insight and eloquence as one of the very few portraits of American slavery produced by someone as educated as Solomon Northup, or by someone with the dual perspective of having been both a free man and a slave.--Page [4] of cover.